Health systems efficiency in China and ASEAN, 2015–2020: a DEA-Tobit and SFA analysis application - Jing Kang; Rong Peng; Zhen Li; Fen Huang; Yujun Chen; Jun Feng; Junyuan Wei; Fu Yu; Xiaorong Su; Xianjing Qin; Qiming Feng (BMJ Open)
Objective To evaluate the health systems efficiency in China and Association of Southeast Asian Nations (ASEAN) countries from 2015 to 2020.Design Health efficiency analysis using data envelopment analysis (DEA) and stochastic frontier approach analysis.Setting Health systems in China and ASEAN countries.Methods DEA-Malmquist model and SFA model were used to analyse the health system efficiency among China and ASEAN countries, and the Tobit regression model was employed to analyse the factors affecting the efficiency of health system among these countries.Results In 2020, the average technical efficiency, pure technical efficiency and scale efficiency of China and 10 ASEAN countries’ health systems were 0.700, 1 and 0.701, respectively. The average total factor productivity (TFP) index of the health systems in 11 countries from 2015 to 2020 was 0.962, with a decrease of 1.4%, among which the average technical efficiency index was 1.016, and the average technical progress efficiency index was 0.947. In the past 6 years, the TFP index of the health system in Malaysia was higher than 1, while the TFP index of other countries was lower than 1. The cost efficiency among China and ASEAN countries was relatively high and stable. The per capita gross domestic product (current US$) and the urban population have significant effects on the efficiency of health systems.Conclusions Health systems inefficiency is existing in China and the majority ASEAN countries. However, the lower/middle-income countries outperformed high-income countries. Technical efficiency is the key to improve the TFP of health systems. It is suggested that China and ASEAN countries should enhance scale efficiency, accelerate technological progress and strengthen regional health cooperation according to their respective situations.